THE ANALYSIS CONCEPT PRELIMINARY OF PHYSICS AND THE STUDY RESULT PHYSICS IN LEARNING MODEL BY USING INQUIRY ON TRAINING MATERIALS DYNAMIC ELECTRICAL - Ratni Sirait; Sahyar . (Universitas Negeri Medan, 2013)
This study aims to analyze (1)The results of studying physicsstudent's by learning model Inquiry Training and Direct Instruction. (2)Theresults of studying physics students who have low initial concept mastery andmastery of high initial concept. (3)The interaction between the levels ofmastery learning model with the initial concept in improving learning outcomes Physics. The study population is a private junior high schoolstudent PAB 8 Deli Serdang. The sample is random cluster class. Theinstrument used consisted of (1)initial concept mastery test, (2)Test resultsof learning with dynamic power subject matter. The next stage is to test theprerequisite analysis tests of normality and homogeneity. Results of dataanalysis showed that the samples come from populations that are normallydistributed and variances homogeneous both samples. Then test thehypothesis by using ANOVA analysis of two paths. The results showed that(1)Results of student learning in the classroom Inquiry Training better thanthe class of student learning outcomes Direct Instruction. (2)The results ofstudents' mastery of concepts that have high and low at the beginning ofInquiry Training class is better than mastery of the concept of high and lowinitial class of students in the Direct Instruction. (3)There is no interactionbetween learning model and Direct Instruction Training Inquiry with theinitial level of mastery of concepts in Physics improves learning outcomes.